Penilaian Tingkat Kestabilan Lereng De ngan Metode Slope Mass Rating (SMR) pada Bench S dan J PT Tanjung Bukit Nunggal Kabupaten Bangka Tengah - Evrantino Insani Sitohang; Janiar Pitulima; Haslen Oktarianty (MINERAL, 2022)
Excavation activities on mining activities cause tension changes on the ground that trigger the occurrence of deformation then followed by changes in slope stability. If slope stability is impaired then it will lead to the possibility of an avalanche, this will certainly result in the disruption of mining activities that endanger workers who are on the slope area with potential for avalanches. This study aims to find out parameters of basic RMR and deflection values of basic RMR at bench S and J, find out the values of slope stability using SMR at bench S and J, and cope with slope instability based on SMR values. The methods used in this study are quantitative and qualitative methods namely scanline sampling and rock physical test that is Uniaxial Compressive Strenght (UCS) tests, and Rock Quality Designation (RQD) measurements. The results of this study show that the rock conditions at the bench S and J are still good with RMR values of approximately 71 ± 73, the probability of avalanche occurrence is very low as SMR values range 71 ± 73, but still it needs to be carried out cutting on blocks indicated to ruins.